Multitechnique geochronology of intrusive and explosive activity on Piton des Neiges Volcano, Réunion Island - Famin, Vincent; Paquez, Camille; Danišík, Martin; Gardiner, Nicholas J.; Michon, Laurent; Kirkland, Christopher L.; Berthod, Carole; Friedrichs, Bjarne; Schmitt, Axel Karl; Monié, Patrick (Geochemistry, geophysics, geosystems, 2022)
The construction of ocean island basaltic volcanoes consists of a succession of eruptions, intrusions, and metamorphism. These events are often temporally ill-constrained because the most widely used radiometric dating methods applicable to mafic volcanic rocks (K-Ar or 40Ar/39Ar on whole rock or groundmass) are prone to inaccuracy when applied to slowly cooled, altered, or vesicular and aphyric products. Here, we adopt a multitechnique geochronology approach (including zircon U-Pb, phlogopite 40Ar/39Ar, zircon and apatite (U-Th)/He, and zircon double-dating) to demonstrate its efficacy when applied to basaltic volcanoes. Taking the main volcano of Réunion Island (Piton des Neiges) as a case study, we establish the time of the major plutonic, metamorphic, and explosive events that had resisted previous dating attempts. We document four stages of pluton emplacement and metamorphism at 2,200-2,000 ka, 1,414 ± 8 ka, 665 ± 78 ka, and 150-110 ka, all coinciding with volcanism revival after quiescent intervals. We also date a major Plinian eruption at 188.2 ± 10.4 ka, coeval with the formation age of a large caldera, and, finally, we constrain the last eruption of Piton des Neiges to 27 ka, revising a previous estimate of 12 ka. By resolving several conundrums of Réunion's geological history, our multitechnique geochronology approach reveals that endogenous growth of a volcanic island proceeds as pulses at the beginning of renewed volcanism. We also demonstrate that crosschecking eruptions ages by diversified dating techniques is important to better assess the timing and recurrence of basaltic volcanic activity, with implications for hazard prediction.
First published: 07 March 2022
Gesehen am 27.06.2022